Halal-Based Entrepreneurship Development for Menteng MSME Community Industry - Desmintari; Lina Aryani; Dahlia Pinem (Indonesian Journal of Society Development, 2023)
Menteng District is located in the administrative area of ​​Central Jakarta City, DKI Jakarta Province. Partners who become objects are MSME actors in the Menteng “Naik Kelas” MSME Community. Currently, the development of products produced by MSME actors has not been maximized. This is because partners have not applied the principles of the halal industry to their products. The goal to be achieved from this community service activity is to improve product quality by guiding partners to develop products based on the halal industry. In general, the method of service carried out to partners is in the form of socialization/virtual counseling related to the halal industry and their product development based on the principles of the halal industry. It is hoped that this training can improve competitiveness and product quality so as to increase the sales volume of products made by the Menteng "Naik Kelas" MSME group. Community service activities were carried out on June 18, 2022, attended by 62 “Naik Kelas” MSME participants. Based on the results of community service, participants were very enthusiastic about participating in the activity. Questions and answers and discussions between the abdimas team and the participants took place interactively and constructively. Participants are very interested in applying the principles of the halal industry to their products. The output of this activity is that MSME actors can apply the concept of the halal industry in developing their products independently